2016
DOI: 10.1093/forestry/cpw026
|View full text |Cite
|
Sign up to set email alerts
|

Climate and disturbance regime effects on aspen (Populus tremuloidesMichx.) stand structure and composition along an east–west transect in Canada's boreal forest

Abstract: Stand structure and composition play a key role in maintaining the ecological integrity of the boreal forest. However, future changes in climate and disturbance regime could affect these forest attributes. Using provincial forest inventory datasets, we analysed stands dominated by aspen (≥75% of the plot total basal area) distributed along a wide longitudinal gradient of environmental conditions across Canada. Stands were classified into three diameter structure types (inverted J, intermediate and advanced). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…factors. In terms of abiotic factors, it is commonly accepted that the amount of rainfall is one of the essential factors for plant survival [49][50][51]. Our study supports that statement, in that the diversity and density of natural regeneration increased with rainfall.…”
Section: Discussionsupporting
confidence: 89%
“…factors. In terms of abiotic factors, it is commonly accepted that the amount of rainfall is one of the essential factors for plant survival [49][50][51]. Our study supports that statement, in that the diversity and density of natural regeneration increased with rainfall.…”
Section: Discussionsupporting
confidence: 89%
“…, Nlungu‐Kweta et al. ). In the arid Great Basin, little aspen research has been conducted, but conifer competition and ungulate browsing have been found to contribute to aspen decline (e.g., Strand et al.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important that forests are constantly monitored to determine whether diversity is being maintained. However, although much attention has been given to biodiversity conservation and how biodiversity varies between different forest conditions [1,9], we still only have a limited understanding of how forest diversity and structure vary between different rainfall regions because such forests always occur in different regions with different climates [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%